Effects of different psychological interventions on quality of life and remission rate in patients with acute leukemia receiving chemotherapy: A randomized controlled trial - Peng, Fang; Li, Huiyuan; Zhang, Jingping; Li, Xiaoyun; Zhang, Haimiao; Li, Yifei (Frontiers in Psychology, 2023)
Aims This study aimed to examine and compare different psychological intervention effects on the quality of life (QoL) and remission rates of patients with acute leukemia receiving chemotherapy. Methods A total of 180 participants were randomly divided into a cognitive intervention group, a progressive muscle relaxation (PMR) group, a cognitive intervention plus PMR group, and a usual care control group. QoL via the Chinese version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 and remission rate were assessed at baseline and immediate post-intervention. A Generalized Linear Mixed Model was used for statistical analysis. Cost-effectiveness analysis with the value of the Incremental Cost-effectiveness Ratio was conducted to realize the economic evaluation of psychological interventions. Results The total score of QoL and its most dimensions were significantly improved for participants in the intervention groups compared with the control group. The cognitive intervention plus PMR intervention was the most effective concerning QoL with cost-effectiveness. No significant improvements were indicated in participants’ remission rates among the groups. Conclusion The cognitive intervention plus PMR intervention is the most effective in improving QoL with cost-effectiveness among patients with acute leukemia receiving chemotherapy. More rigorous randomized controlled trials with multiple follow-up points are suggested to clarify the psychological interventions on remission rates in this population.